Electrochemical oxygen reduction catalyst
Patent Information
- Application Number
- JP2025064053
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-22
AI Technical Summary
【0009】 本発明により、高い触媒活性及び高い触媒活性向上効果を示す電気化学的酸素還元触媒を提供することが可能となる。
Smart Images

Figure 2026170515000001_ABST
Abstract
Description
[Technical Field]
[0001] This invention relates to an electrochemical oxygen reduction catalyst. [Background technology]
[0002] Electrochemical oxygen reduction catalysts are widely used in fuel cells, water electrolysis systems, and metal-air batteries, among other applications. Known electrochemical oxygen reduction catalysts include those in which a catalyst metal supported on a carrier is modified with a nitrogen-containing organic compound.
[0003] For example, Patent Document 1 discloses a catalyst comprising metal particles having oxygen-reducing activity, an additive having basic functional groups, and a binder having acidic functional groups, wherein the additive is at least one organic nitrogen compound, and the ratio of the total amount of basic functional groups of the additive to the total amount of acidic functional groups of the binder (basic points / acid points) is greater than 0 and 6.82 or less. Patent Document 1 also discloses that the metal particles may be supported on a carrier.
[0004] Furthermore, Patent Document 2 describes a material comprising metal particles having oxygen-reducing activity, a carrier, and an additive, wherein the metal particles are supported on the carrier, the additive is at least one organic nitrogen compound, and the BET specific surface area of the carrier is 641 m². 2 g -1 support A catalyst characterized by the following is disclosed. [Prior art documents] [Patent Documents]
[0005] [Patent Document 1] Japanese Patent Publication No. 2024-11754 [Patent Document 2] Japanese Patent Publication No. 2024-16321 [Overview of the project] [Problems that the invention aims to solve]
[0006] As described above, electrochemical oxygen reduction catalysts containing a catalytic metal supported on a carrier are known. However, with conventional catalysts, depending on the carrier used, sufficient catalytic activity improvement effects by modifying the catalytic metal with additives may not be obtained, and high catalytic activity may not be obtained. Therefore, the present invention aims to provide an electrochemical oxygen reduction catalyst that exhibits high catalytic activity and a high catalytic activity improvement effect. [Means for solving the problem]
[0007] The inventors of the present invention have discovered that catalytic activity and catalytic activity enhancement effects can be improved by controlling the properties of the mesoporous carbon support, and have completed the present invention.
[0008] In other words, the present invention encompasses the following aspects and embodiments. (Embodiment 1) comprising a catalyst metal having oxygen reduction activity supported on mesoporous carbon, and a modification layer that modifies the catalyst metal, The mode diameter of the primary particles of the mesoporous carbon is 700 nm or less. The aforementioned mesoporous carbon is as follows: a)~c): a) BET specific surface area is 641 m² 2 g -1 ; b) Mode pore size is less than 7.7 nm; c) Total pore volume of pores in the range of 2.0 nm to 30 nm is 6.50 mL g -1 bigger An electrochemical oxygen reduction catalyst that satisfies at least one of the following conditions. (Embodiment 2) The electrochemical oxygen reduction catalyst according to Embodiment 1, wherein the mode diameter of the primary particles of the mesoporous carbon is 300 nm or less. (Embodiment 3) comprising a catalyst metal having oxygen reduction activity supported on mesoporous carbon, and a modification layer that modifies the catalyst metal, The median diameter of the primary particles of the mesoporous carbon is 750 nm or less. The aforementioned mesoporous carbon is as follows: a)~c): a) The BET specific surface area is 641 m 2 g -1 greater than; b) The mode pore diameter is less than 7.7 nm; c) The total pore volume of pores in the range of 2.0 nm to 30 nm is 6.50 mL g -1 greater than An electrochemical oxygen reduction catalyst that satisfies at least one of the above. (Embodiment 4) The electrochemical oxygen reduction catalyst according to Embodiment 3, wherein the median diameter of the primary particles of the mesoporous carbon is 400 nm or less. (Embodiment 5) The electrochemical oxygen reduction catalyst according to any one of Embodiments 1 to 4, wherein the catalytic metal is platinum, a platinum alloy or a composite containing platinum, and the modification layer contains a nitrogen-containing cyclic organic compound, a polymer thereof, or a cation thereof. [Advantageous Effects of the Invention]
[0009] According to the present invention, it is possible to provide an electrochemical oxygen reduction catalyst that exhibits high catalytic activity and a high catalytic activity improving effect. [Brief Description of the Drawings]
[0010] [Figure 1] This is a graph showing the relationship between the mode diameter of primary particles of a carbon support and the mass activity improvement ratio of the catalyst. [Figure 2] This is a graph showing the relationship between the median diameter of primary particles of a carbon support and the mass activity improvement ratio of the catalyst. [Modes for Carrying Out the Invention]
[0011] Hereinafter, preferred embodiments of the present invention will be described in detail.
[0012] <Electrochemical Oxygen Reduction Catalyst> One aspect of the present invention relates to an electrochemical oxygen reduction catalyst. The electrochemical oxygen reduction catalyst of this aspect (hereinafter also referred to as the catalyst of this aspect) comprises a catalytic metal having oxygen reduction activity supported on mesoporous carbon and a modification layer that modifies the catalytic metal. That is, the catalyst of this aspect comprises a mesoporous carbon support, a catalytic metal having oxygen reduction activity, and a modification layer.
[0013] In the first embodiment of the catalyst according to this specification, the mode diameter of the primary particles of mesoporous carbon is 700 nm or less.
[0014] In the second embodiment of the catalyst according to this specification, the median diameter of the primary particles of mesoporous carbon is 750 nm or less.
[0015] The configurations of the first and second embodiments of the catalyst according to this embodiment will be described below.
[0016] In the catalyst of this embodiment, the catalyst metal may be any metal having oxygen reduction activity (oxygen reduction catalytic ability). Examples of catalyst metals include platinum, ruthenium, iridium, rhodium, palladium, osmium, tungsten, lead, iron, chromium, cobalt, nickel, manganese, vanadium, molybdenum, gallium, aluminum, lanthanum, cerium, praseodymium, neodymium, samarium, gadolinium, and yttrium. The catalyst metal may consist of one of the metals exemplified above, or it may consist of two or more metals as an alloy. The catalyst metal may also be an oxide, nitride, sulfide, or phosphide of the metals exemplified above. Preferably, the catalyst metal is platinum, a platinum alloy, or a composite containing platinum. In the case of platinum alloys and composites containing platinum, examples of metals other than platinum include ruthenium, iridium, and cobalt. When the catalyst metal is a platinum alloy or a platinum-containing composite, the content of metals other than platinum is typically in the range of 0.11 to 60 atomic percent relative to the total mass of the catalyst metal.
[0017] The loading ratio of the catalyst metal is typically in the range of 1 to 70 mass% relative to the mass of the mesoporous carbon, for example, in the range of 18 to 48 mass%.
[0018] The particle size (diameter) of the catalytic metal is typically in the range of 1 nm to 100 nm.
[0019] In the catalyst of this embodiment, the composition and content of the catalyst metal can be determined, for example, by analysis using thermogravimetric analysis (TG) or inductively coupled plasma emission spectroscopy (ICP).
[0020] In the catalyst of this embodiment, the particle size of the catalyst metal can be determined, for example, by measuring the crystallite size by X-ray diffraction and calculating the average crystallite size. Alternatively, the particle size of the catalyst metal may be determined by measuring the particle sizes of 100 to 1000 catalyst metal particles using an electron microscope and calculating the average value (average particle size).
[0021] In the catalyst of this embodiment, the catalyst metal is supported on mesoporous carbon (carbon support). In this disclosure, mesoporous carbon is carbon having pores. In the catalyst of this embodiment, the catalyst metal is usually supported inside the pores of the mesoporous carbon, and may also be supported on the surface of the mesoporous carbon. In one embodiment, the catalyst metal is supported inside the pores of the mesoporous carbon and also supported on the surface of the mesoporous carbon.
[0022] Conventional methods can be used to support the catalyst metal on mesoporous carbon. For example, one method involves mixing the catalyst metal with a mesoporous carbon dispersion, filtering and washing the dispersion, redispersing it in ethanol or the like, and then drying it using a vacuum pump or the like. After drying, heat treatment may be performed as needed.
[0023] In the catalyst of this embodiment, the mesoporous carbon contains primary particles having pores. Primary particles are the smallest units of particles that cannot be decomposed. The mesoporous carbon may also contain secondary particles formed by aggregation of primary particles having pores, as long as it contains primary particles having pores. The presence of pores in the primary particles can be confirmed, for example, by observation using an electron microscope.
[0024] In the first embodiment of the catalyst according to this specification, the mode diameter of the primary particles of mesoporous carbon is 700 nm or less. When the catalyst metal is supported inside the pores of the support, the distance from the support surface to the catalyst metal becomes long, making it difficult to modify the catalyst metal with the modification layer containing additives, and thus difficult to exhibit the catalytic activity improvement effect. When the mode diameter of the primary particles of mesoporous carbon is 700 nm or less, it becomes easier to modify the catalyst metal with the modification layer, and the catalytic activity improvement effect is enhanced. The mode diameter of the primary particles of mesoporous carbon may be 300 nm or less, or 100 nm or less, or 50 nm or less. When the mode diameter of the primary particles of mesoporous carbon is within this range, the catalytic activity improvement effect is further enhanced. The lower limit of the mode diameter of the primary particles of mesoporous carbon is not particularly limited, and may be, for example, 5 nm or more, or 10 nm or more, or 20 nm or more. The mode diameter of the primary particles of mesoporous carbon may be, for example, 5 nm to 700 nm, or 10 nm to 300 nm. The mode diameter of primary particles in mesoporous carbon refers to the particle size (also called the peak diameter) with the highest peak in the particle size distribution (number-based) obtained by the measurement method described below.
[0025] In the second embodiment of the catalyst according to this embodiment, the median diameter of the primary particles of mesoporous carbon is 750 nm or less. When the median diameter of the primary particles of mesoporous carbon is 750 nm or less, it becomes easier to modify the catalyst metal with the modification layer, and the catalytic activity improvement effect is enhanced. The median diameter of the primary particles of mesoporous carbon may be 400 nm or less, 350 nm or less, or 80 nm or less. When the median diameter of the primary particles of mesoporous carbon is within this range, the catalytic activity improvement effect is further enhanced. The lower limit of the median diameter of the primary particles of mesoporous carbon is not particularly limited, and may be, for example, 5 nm or more, 10 nm or more, or 20 nm or more. The median diameter of the primary particles of mesoporous carbon may be, for example, 5 nm to 750 nm, or 10 nm to 400 nm. The median diameter of primary particles in mesoporous carbon refers to the 50% cumulative particle diameter (also known as D50) in the particle size distribution (based on particle count) obtained by the measurement method described below.
[0026] The mode diameter and median diameter of primary particles of mesoporous carbon can be measured using, for example, a transmission electron microscope (TEM), a scanning electron microscope (SEM), laser diffraction, light scattering, dynamic light scattering (DLS), centrifugal sedimentation, and particle trajectory analysis (PTA). These measurement methods may be combined. For example, the particle size of 100 to 1000 primary particles of mesoporous carbon may be measured using TEM or SEM, and the mode diameter and median diameter in the resulting particle size distribution may be taken as the mode diameter and median diameter of the primary particles of mesoporous carbon, respectively. In one embodiment, the mode diameter and median diameter of primary particles of mesoporous carbon can be measured by TEM and laser diffraction.
[0027] In one embodiment, the mesoporous carbon may have both the mode diameter of the primary particles in the first embodiment and the median diameter of the primary particles in the second embodiment. That is, in one embodiment, the mesoporous carbon has a mode diameter of primary particles of 700 nm or less and a median diameter of primary particles of 750 nm or less.
[0028] In the catalyst of this embodiment, the mesoporous carbon is as follows: a) to c): a) BET specific surface area is 641 m² 2 g -1 ; b) Mode pore size is less than 7.7 nm; c) Total pore volume of pores in the range of 2.0 nm to 30 nm is 6.50 mL g -1 bigger It satisfies at least one of the following. Mesoporous carbon satisfies one, two, or three of the above a) to c), and may satisfy two or three, and in one embodiment, satisfies all three of the above a) to c).
[0029] Regarding a) above, mesoporous carbon has a BET specific surface area of 641 m². 2 g -1 Larger, 650m 2 g -1 It may be larger. In the catalyst of this embodiment, catalytic activity is high when the BET specific surface area of the mesoporous carbon is within this range. Note that the BET specific surface area is the value relative to the mass of the mesoporous carbon (m 2 g -1 メソポーラスカーボン )
[0030] Regarding b) above, the mode pore diameter of the mesoporous carbon may be less than 7.7 nm and less than 7.0 nm. In the catalyst of this embodiment, catalytic activity is high when the mode pore diameter of the mesoporous carbon is within this range. Note that pore diameter refers to the diameter of the pore. Furthermore, the mode pore diameter of the mesoporous carbon refers to the pore diameter with the highest peak (also called the peak pore diameter) in the pore distribution curve obtained by the measurement method described below.
[0031] Regarding c) above, the mesoporous carbon has a total pore volume of 6.50 mL g of pores in the range of 2.0 nm to 30 nm. -1 Larger, 7.0 mL g -1It may be larger. In the catalyst of this embodiment, catalytic activity is high when the total pore volume of the mesoporous carbon is within this range. The total pore volume is the total pore volume (mL g) of pores with a pore diameter in the range of 2.0 nm to 30 nm relative to the mass of the mesoporous carbon. -1 メソポーラスカーボン ) refers to.
[0032] Regarding the physical properties of the mesoporous carbon (support), the support may be measured directly, or the support bearing the catalyst metal may be measured and converted to the mass of the support. The BET specific surface area, mode pore diameter, and total pore volume in the range of 2.0 nm to 30 nm can all be measured by the N2 adsorption / desorption method. The above three parameters may also be obtained from the relative pressure dependence of the amount of N2 adsorbed onto the sample. The BET theory is used to calculate the specific surface area. The evaluation method is not limited to the above, and may also be evaluated by Hg porosimetry, H2O adsorption, DBP supply using dibutyl phthalate, etc. Microscopic observation may also be used.
[0033] In the catalyst of this embodiment, the mesoporous carbon content can be determined, for example, by analysis using thermogravimetric analysis (TG) or inductively coupled plasma emission spectroscopy (ICP).
[0034] In the catalyst of this embodiment, the modification layer may contain a nitrogen-containing cyclic organic compound or a polymer thereof, or cations thereof. In the catalyst of this embodiment, the electrochemical oxygen reduction reaction is promoted by modifying the catalyst metal with a modification layer containing a nitrogen-containing cyclic organic compound or a polymer thereof, or cations thereof, as an additive (modifier).
[0035] In the catalyst of this embodiment, the nitrogen-containing cyclic organic compound may be, for example, a compound having a 3-20 membered ring or a 3-10 membered ring having 1, 2, 3, 4, or 5 nitrogen atoms in the ring, or a compound having a 5 or 6 membered ring. The nitrogen-containing cyclic organic compound may be a monocyclic or polycyclic compound. If the nitrogen-containing cyclic organic compound is a polycyclic compound, it is sufficient that at least one ring has nitrogen atoms. The nitrogen-containing cyclic organic compound is not particularly limited and can include, for example, piperidine, piperazine, morpholine, quinuclidine, pyrrolidine, azetidine, azetidine-2-one, aziridine, tropane, pyrrole, imidazole, pyrazole, oxazole, isoxazole, thiazole, isothiazole, pyridine, pyrimidine, pyridazine, pyrazine, triazine, quinoline, isoquinoline, quinazoline, phthalazine, pteridine, 1,4-benzodiazepine, indole, benzimidazole, purine, acridine, phenoxazine, phenothiazine and their derivatives, as well as organic compounds containing these skeletons in part. In one embodiment, the nitrogen-containing cyclic organic compound is a compound having a triazine skeleton (1,2,3-triazine, 1,2,4-triazine, or 1,3,5-triazine) from the viewpoint of durability.
[0036] In one embodiment, the nitrogen-containing cyclic organic compound or its polymer or cation thereof is a compound represented by general formula (1), a polymer with the compound as a monomer, or a cation thereof.
[0037] [ka] (In the formula, R1, R2 and R3 are, respectively, a hydrogen atom, a halogen atom, a nitrile group, an amide group, an imine group, an amino group, a thiol group, a hydroxyl group, a sulfo group, a carboxylic acid group, a phosphoric acid group, a ketone group, an aldehyde group, an ester group, an alkoxy group, a phenol group, a cyclopentyl group, a cyclohexyl group, a C1-C10 alkylamino group, a C1-C10 alkylsulfonic acid group, a C1-C10 perfluoroalkyl group, a C1-C10 alkyl group, and a C2-C10 alkyl group.) The functional group is selected from the group of functional groups consisting of an alkenylamino group, an alkenylsulfonic acid group having 2 to 10 carbon atoms, a perfluoroalkenyl group having 2 to 10 carbon atoms, and an alkenyl group having 2 to 10 carbon atoms. Each of these functional groups may have at least one selected from the group consisting of at least one functional group selected from the aforementioned group of functional groups, an aromatic ring, a heterocycle, an oxygen atom, a sulfur atom, a nitrogen atom, a fluorine atom, a chlorine atom, a bromine atom, an iodine atom, and a hydrogen atom in its molecular chain.
[0038] Nitrogen-containing cyclic organic compounds or their polymers or their cations (hereinafter also referred to as nitrogen-containing cyclic organic compounds, etc.) may be melamine (1,3,5-triazine-2,4,6-triamine), ammelin, ammerido, cyanuric acid, thiocyanuric acid, triazine (1,2,3-triazine, 1,2,4-triazine, or 1,3,5-triazine) or its derivatives or polymers or their cations. Furthermore, the nitrogen-containing cyclic organic compound may be 2,4,6-tris[bis(methoxymethyl)amino]-1,3,5-triazine, 6-(dibutylamino)-1,3,5-triazine-2,4-dithiol, 2,4-diamino-6-butylamino-1,3,5-triazine, or 2,4,6-tris(pentafluoroethyl)-1,3,5-triazine, or polymers using these as monomers, or copolymers such as methylated poly(melamine-coformaldehyde) or isobutylated poly(melamine-coformaldehyde), or cations thereof. In one embodiment, the nitrogen-containing cyclic organic compound is melamine or its derivatives, or its polymers, or cations thereof.
[0039] The content of the modification layer is typically in the range of 0.001 to 0.1 as a mass ratio to the mass of the catalyst metal in the catalyst of this embodiment.
[0040] The composition and content of nitrogen-containing cyclic organic compounds or polymers thereof, or their cations, contained in the modified layer can be determined, for example, by dissolving and extracting the modified layer contained in the catalyst of this embodiment, and analyzing the components contained in the extract by elemental analysis, various types of chromatography, ultraviolet-visible spectroscopy (UV-Vis), infrared spectroscopy (IR), or nuclear magnetic resonance (NMR).
[0041] In the catalyst of this embodiment, the modification layer is usually disposed on the surface of the catalyst metal, for example, by coating the surface of the catalyst metal. The modification rate of the modification layer on the surface of the catalyst metal may be 8 area % or more, and may be 11 area % or more, 12 area % or more, or 20 area % or more, relative to the total surface area of the catalyst metal. A modification rate of 8 area % or more enhances the catalytic activity improvement effect. The upper limit of the modification rate of the modification layer on the surface of the catalyst metal is not particularly limited, and may be, for example, 50 area % or less, 40 area % or less, or 30 area % or less. The modification rate of the modification layer on the surface of the catalyst metal is defined as the percentage of the surface area of the catalyst metal modified by the modification layer relative to the total surface area of the catalyst metal. The modification rate of the modification layer on the surface of the catalyst metal can be determined, for example, by the method described in the examples.
[0042] The catalyst in this embodiment may contain a binder. The binder is usually a polymer electrolyte (ionomer) having ion exchange groups. Examples of ion exchange groups contained in the polymer electrolyte include sulfonic acid groups and phosphate groups. The binder is, for example, a perfluorocarbon sulfonic acid polymer.
[0043] <Applications of electrochemical oxygen reduction catalysts> Another aspect of the present invention relates to a fuel cell. The fuel cell of this aspect comprises at least a cathode electrode catalyst layer, an anode electrode catalyst layer, and an electrolyte membrane disposed between the cathode electrode catalyst layer and the anode electrode catalyst layer, wherein the cathode electrode catalyst layer includes an electrochemical oxygen reduction catalyst according to one aspect of the present invention.
[0044] Yet another aspect of the present invention relates to a water electrolysis system. The water electrolysis system of this aspect comprises at least a cathode electrode catalyst layer, an anode electrode catalyst layer, an electrolyte membrane disposed between the cathode electrode catalyst layer and the anode electrode catalyst layer, and a water supply unit, wherein the anode electrode catalyst layer includes an electrochemical oxygen reduction catalyst according to one aspect of the present invention.
[0045] A further aspect of the present invention relates to a metal-air battery. The metal-air battery of this aspect comprises at least a cathode electrode catalyst layer, an anode metal layer, and an electrolyte membrane disposed between the cathode electrode catalyst layer and the anode metal layer, wherein the cathode electrode catalyst layer comprises an electrochemical oxygen reduction catalyst according to one aspect of the present invention.
[0046] <Method for producing an electrochemical oxygen reduction catalyst> Another aspect of the present invention relates to a method for producing an electrochemical oxygen reduction catalyst according to an aspect of the present invention. The method of this aspect includes a modification step. The method of this aspect may optionally include a preparation step and an electrode catalyst layer fabrication step.
[0047] [Preparation process] This process includes preparing mesoporous carbon (support), catalyst metal, and additives. This process usually also includes preparing a binder. Furthermore, this process may optionally include preparing additional materials such as solvents and substrates. Each material prepared in this process only needs to have the characteristics described above. In this process, each material may be prepared by the manufacturer themselves to have the predetermined characteristics, or it may be prepared by purchasing commercially available products. The catalyst metal can be supported on the mesoporous carbon by conventional methods. Note that the support of the catalyst metal on the mesoporous carbon may be carried out in a later modification step by mixing the mesoporous carbon, catalyst metal, and additives.
[0048] [Modification process] This process involves mixing a catalyst metal supported on mesoporous carbon with an additive to modify the catalyst metal with a modified layer containing the additive. In this process, a binder may optionally be mixed together with the catalyst metal and additive. In this process, the catalyst metal supported on mesoporous carbon, the additive, and optionally the binder are usually mixed together with a solvent. The solvent is not particularly limited and can include, for example, water and alcohol (e.g., 2-propanol), and mixtures of one or more thereof.
[0049] In this process, by removing the solvent from the resulting mixture, an electrochemical oxygen reduction catalyst according to one embodiment of the present invention can be obtained.
[0050] Alternatively, when carrying out the electrode catalyst layer fabrication process described below, the mixture obtained in this process can be used in the electrode catalyst layer fabrication process as a catalyst ink containing an electrochemical oxygen reduction catalyst according to one embodiment of the present invention. In this case, the mixture obtained in this process may be used as is, or it may be used with the solvent exemplified above further added.
[0051] [Electrode catalyst layer fabrication process] This step involves coating the surface of a substrate with a catalyst ink containing the electrochemical oxygen reduction catalyst obtained in the modification step. In this step, the solvent is usually removed from the catalyst ink after coating.
[0052] The substrate used in this process is not particularly limited, and any material such as polytetrafluoroethylene (PTFE), electrolyte membranes having ion exchange groups, carbon fibers, and metal fibers can be used.
[0053] By carrying out this process, an electrochemical oxygen reduction catalyst according to one embodiment of the present invention can be obtained in a form (electrode catalyst layer) arranged on the surface of a substrate. In this case, the thickness of the electrode catalyst layer is usually in the range of 5 to 30 μm. Furthermore, the content of the catalyst metal in the electrode catalyst layer is usually 0.1 to 0.6 mg / cm² as mass relative to the total area of the electrode catalyst layer. 2 It is within the range. [Examples]
[0054] The present invention will be described in more detail below using examples. However, the technical scope of the present invention is not limited to these examples.
[0055] <Manufacturing of electrochemical oxygen reduction catalysts> [Examples 1-7 and Comparative Examples 1-7] Mesoporous carbon (carbon carriers) with different properties, as shown in Table 1, were prepared. The BET specific surface area, mode pore diameter, and total pore volume in the range of 2.0 nm to 30 nm of the carbon carriers were measured as described above. The mode diameter and median diameter of the primary particles of the carbon carriers are number-based values measured by transmission electron microscopy (TEM) and laser diffraction.
[0056] Platinum particle-supported supports were prepared by supporting platinum particles on each carbon support.
[0057] A catalyst ink containing an electrochemical oxygen reduction catalyst was prepared by adding predetermined amounts of the above-mentioned platinum particle support, melamine (additive), perfluorocarbon sulfonic acid polymer (Nafion (Chemours) based, EW: 1100), and a mixed solvent of 2-propanol and ultrapure water to a container, mixing and stirring. In the electrochemical oxygen reduction catalyst, the platinum particles were modified with a modification layer containing melamine.
[0058] <Evaluation of electrochemical oxygen reduction catalysts> [Catalyst performance] Catalyst performance is measured by the catalyst mass activity (A g) at a potential of 0.9 V (vs. RHE). -1 The catalytic mass activity was evaluated using the following method. Catalytic mass activity represents the current per unit mass of metal particles; a higher value indicates higher catalytic activity.
[0059] The catalyst ink was prepared with a support weight of 20 μg cm³. -2 To achieve this, a glassy carbon rotating electrode (5 mm in diameter) (manufactured by Hokuto Denko Co., Ltd.) was dropped onto the electrode, dried, and an electrode with a catalyst layer formed on its surface was fabricated.
[0060] Electrochemical measurements were performed using a three-electrode system, with the fabricated electrode as the working electrode, a reversible hydrogen electrode as the reference electrode, and a carbon rod as the counter electrode. The electrochemical measurements were performed using the rotary electrode (RDE) method. A 0.1 M perchloric acid aqueous solution prepared with ultrapure water was used as the electrolyte. After performing cyclic voltammetry under an inert gas atmosphere, the gas atmosphere was changed to oxygen, and linear sweep voltammetry was performed from the low potential side. The electrode rotation speed was changed to 400, 900, 1600, 2000, 2500, and 3600 rpm, and the linear sweep voltammetry measurements were repeated. From the obtained potential-current characteristics, a Kouteckey-Levich plot was created, and the catalyst mass activity (A g) at 0.9 V (vs. RHE) was calculated. -1 The ratio of improvement in catalyst mass activity due to modification with an additive-containing modification layer (mass activity improvement ratio) was calculated using the following formula: (catalyst mass activity after additive introduction) / (catalyst mass activity before additive introduction). In addition, the current density was calculated from the potential-current characteristics at 0.2 A cm⁻¹.-2 The cell potential (cell voltage) was recorded.
[0061] [Surface modification rate] For electrochemical oxygen reduction catalysts, the ratio of the surface area of platinum particles modified with a modification layer to the total surface area of platinum particles (surface modification rate) was determined using the hydrogen adsorption current value of the reduction wave in a cyclic voltammogram.
[0062] Table 1 shows the characteristics of the carbon support and the evaluation results of the catalysts from Examples 1-7 and Comparative Examples 1-7. Figure 1 shows the relationship between the mode diameter of the primary particles of the carbon support and the mass activity improvement ratio of the catalyst for Examples 1-7 and Comparative Examples 1-4. Figure 2 shows the relationship between the median diameter of the primary particles of the carbon support and the mass activity improvement ratio of the catalyst for Examples 1-7 and Comparative Examples 1-4.
[0063] [Table 1]
[0064] As shown in Table 1 (Examples 1-7 and Comparative Examples 1-4), the surface modification rate increased as the mode diameter and median diameter of the primary particles of the carbon support decreased.
[0065] As shown in Table 1 and Figure 1, the smaller the mode diameter of the primary particles of the carbon support, the higher the mass activity improvement ratio of the catalyst. In particular, the catalysts of Examples 1 to 7, in which the mode diameter of the primary particles of the carbon support was 700 nm or less, had a mass activity improvement ratio of over 1.0, showing a higher catalytic activity improvement effect compared to the catalysts of Comparative Examples 1 to 4, in which the mode diameter of the primary particles of the carbon support was greater than 700 nm.
[0066] As shown in Table 1 and Figure 2, the smaller the median diameter of the primary particles of the carbon support, the higher the mass activity improvement ratio of the catalyst. In particular, the catalysts of Examples 1 to 7, in which the median diameter of the primary particles of the carbon support was 750 nm or less, had a mass activity improvement ratio of over 1.0, showing a higher catalytic activity improvement effect compared to the catalysts of Comparative Examples 1 to 4, in which the median diameter of the primary particles of the carbon support was greater than 750 nm.
[0067] The catalysts in Comparative Examples 5-7 had BET specific surface area, mode pore diameter, and total pore capacity in the range of 2.0 nm to 30 nm of the carbon support outside the range of values specified for an electrochemical oxygen reduction catalyst according to one embodiment of the present invention. As shown in Table 1, although the catalysts in Comparative Examples 5-7 had high mass activity improvement ratios, they had low cell voltages and low catalytic activity.
[0068] It should be noted that the present invention is not limited to the embodiments described above, and various modifications are included. For example, the embodiments described above are described in detail to make the present invention easier to understand, and are not necessarily limited to those having all the configurations described. In addition, it is possible to add, delete, and / or replace some of the configurations in each embodiment with other configurations.
Claims
1. The material comprises a catalyst metal having oxygen reduction activity supported on mesoporous carbon, and a modification layer that modifies the catalyst metal. The mode diameter of the primary particles of the mesoporous carbon is 700 nm or less. The aforementioned mesoporous carbon is as follows: a) to c): a) BET specific surface area is 641 m² 2 g -1 Larger; b) Mode pore size is less than 7.7 nm; c) Total pore volume of pores in the range of 2.0 nm to 30 nm is 6.50 mL g -1 bigger An electrochemical oxygen reduction catalyst that satisfies at least one of the following conditions.
2. The electrochemical oxygen reduction catalyst according to claim 1, wherein the mode diameter of the primary particles of the mesoporous carbon is 300 nm or less.
3. The material comprises a catalyst metal having oxygen reduction activity supported on mesoporous carbon, and a modification layer that modifies the catalyst metal. The median diameter of the primary particles of the mesoporous carbon is 750 nm or less. The aforementioned mesoporous carbon is as follows: a) to c): a) BET specific surface area is 641 m² 2 g -1 Larger; b) Mode pore size is less than 7.7 nm; c) Total pore volume of pores in the range of 2.0 nm to 30 nm is 6.50 mL g -1 bigger An electrochemical oxygen reduction catalyst that satisfies at least one of the following conditions.
4. The electrochemical oxygen reduction catalyst according to claim 3, wherein the median diameter of the primary particles of the mesoporous carbon is 400 nm or less.
5. The electrochemical oxygen reduction catalyst according to claim 1 or 3, wherein the catalyst metal is platinum, a platinum alloy, or a composite containing platinum, and the modification layer contains a nitrogen-containing cyclic organic compound or a polymer thereof, or cations thereof.
Citation Information
Patent Citations
Catalyst
JP2024011754A
Catalyst
JP2024016321A